Ecological and Economic Consequences of Ignoring Jellyfish: A Plea for Increased Monitoring of Ecosystems. Issue 11 (1st November 2016) - Brodeur, Richard D.; Link, Jason S.; Smith, B. E.; Ford, M. D.; Kobayashi, D. R.; Jones, T. T.
Abstract : Gelatinous zooplankton can dominate the dynamics of marine ecosystems; can have major ecological, social, and economic impacts; are often indicative of broader ecosystem perturbations; and are increasingly being harvested by humans. Yet fisheries scientists typically do not monitor these taxa on a regular basis, despite the existence of clear rationales and even mandated authorizations to do so. Notably, the costs of monitoring jellyfish during regular fisheries research cruises would be a small increase over the cost of running a large fishery survey and a small fraction of the costs caused by impacts from these taxa. As ecosystems experience increasing pressures from climate change and fisheries, we recommend considering routine monitoring before some future jellyfish-associated crisis arises.